Grape-Derived Polyphenols Prevent Doxorubicin-Induced Blunted EDH-Mediated Relaxations in the Rat Mesenteric Artery: Role of ROS and Angiotensin II. (27th August 2013) - Idris-Khodja, Noureddine; Di Marco, Paola; Farhat, Mona; Geny, Bernard; Schini-Kerth, Valérie B.
Abstract : This study determined whether doxorubicin, an anticancer agent, impairs endothelium-dependent relaxations mediated by nitric oxide (NO) and endothelium-derived hyperpolarization (EDH) in the mesenteric artery and, if so, the mechanism underlying the protective effect of red wine polyphenols (RWPs), a rich natural source of antioxidants. Male Wistar rats were assigned into 4 groups: control, RWPs, doxorubicin, and doxorubicin + RWPs. Vascular reactivity was assessed in organ chambers; the vascular formation of reactive oxygen species (ROS) using dihydroethidine and the expression levels of small and intermediate conductance calcium-activated potassium channels (S K Ca, I K Ca ) and connexin 40 (Cx40), which are involved in EDH-type relaxations, endothelial NO synthase (eNOS), angiotensin II, and AT1 receptors by immunofluorescence. The doxorubicin treatment impaired EDH-mediated relaxations, whereas those mediated by NO were minimally affected. This effect was associated with reduced expression levels of S K Ca, I K Ca, and Cx40, increased expression levels of eNOS, angiotensin II, and AT1 receptors, and formation of ROS in mesenteric arteries. RWPs prevented both the doxorubicin-induced blunted EDH-type relaxations and the increased vascular oxidative stress, and they improved the expression levels of target proteins. These findings suggest that polyphenol-rich natural products might be of interest in the management of doxorubicin-induced vascular injury possibly by improving the vascular angiotensin system.